Two Dimensional (2d) Nanofabrication Process On Quartz Substrate - Shamsuddin, Nur Liyana Mohd (2016)
The fabrication of nanostructures on a quartz substrate has attracted the attention and interest of researchers in recent years due to its wide range of potential applications such as for NEMS/MEMS including BioMEMS/BioNEMS, sensor and fuel cell electrodes. It would create several new potential due to the excellent properties of quartz in hardness, ability to withstand high temperatures, having high UV transmission and piezoelectric properties- which is a capability to develop an electric potential upon the application of mechanical stress. However, there is limited information of 2D fabricating process on insulating materials such as quartz substrate. Various types of modern lithography methods have been explored because optical lithography physical limitations have hindered the fabrication of nanostructure. Electron beam lithography (EBL) is one of the most commonly used techniques for direct patterning at the nanoscale meter range that enables the nanofabrication of structures and devices in the research field about nanoscience and nanotechnology. The reactive ion etching (RIE) method is usually utilized in process transfer of 2D or 3D structures due to the ability of directional etching. Combination of inductively coupled plasma (ICP) with reactive ion etching (RIE) could boost the densities of the plasma and enhance etch rate during pattern transfer process. The fundamental study conducted in this research can contributes to the existing knowledge and understanding on this crucial process in nanofabrication technology. In this study, a top-down fabrication approach was applied. In this approach, pattern definition process uses the EBL tool and pattern transfer process by inductively coupled plasma-reactive ion etching (ICP-RIE) system. The additive pattern transfer method required for quartz etching, where high resistant mask material was used during etching process. The factors that influenced the pattern definition process, including the selection of photoresist, e-beam exposure parameters such as current, dosage and the developing time were optimised. Meanwhile, the effect of etching parameters ICP-RIE power and flow rate of etchant gases were investigated during the pattern transfer process. A single pass line design was defined on bi-layer polymethyl methacrylate (PMMA). An e-beam dosage of 900 pC/cm was found suitable for pattern definition on a 200 nm PMMA and was successfully deposited with nichrome (NiCr) thin film. With that, a 2D pattern was successfully transferred onto quartz substrate using trifluoromethane (CHF3) and argon (Ar) gases with etching rate of 14 nm/min. The optical microscopy, atomic force microscope (AFM), field emission scanning electron microscopy (FESEM) and energy-dispersive X-ray (EDX) were used to characterize the etched structure profiles.